The effect of player contact characteristics on head impact exposure in youth football games - DiGuglielmo, D. M.; Kelley, M. E.; Espeland, M. A.; Gregory, Z. A.; Payne, T. D.; Jones, D. E.; Filben, T. M.; Powers, A. K.; Stitzel, J. D.; Urban, J. E. (Journal of Applied Biomechanics, 2021)
To reduce head impact exposure (HIE) in youth football, further understanding of the context in which head impacts occur and the associated biomechanics is needed. The objective of this study was to evaluate the effect of contact characteristics on HIE during player versus player contact scenarios in youth football. Head impact data and time-synchronized video were collected from 4 youth football games over 2 seasons in which opposing teams were instrumented with the Head Impact Telemetry (HIT) System. Coded contact characteristics included the player`s role in the contact, player speed and body position, contact height, type, and direction, and head contact surface. Head accelerations were compared among the contact characteristics using mixed-effects models. Among 72 instrumented athletes, 446 contact scenarios (n = 557 impacts) with visible opposing instrumented players were identified. When at least one player had a recorded impact, players who were struck tended to have higher rotational acceleration than players in striking positions. When both players had a recorded impact, lighter players and taller players experienced higher mean head accelerations compared with heavier players and shorter players. Understanding the factors influencing HIE during contact events in football may help inform methods to reduce head injury risk.